MARKETING FOR INNOVATIVE PRODUCT DEVELOPMENT: PERFECTION SEARCH - B. Tokarev (Вестник университета)
The proposed material is a logical continuation of publications on the marketing of innovative startups. The article discusses an important stage of seed - prototype development and testing. The testing process is cyclical in nature. As product characteristics changes it is require to assess their necessity. Key element of startup’s stage is testing the product by future consumers. The tasks that must be solved by prototypes are defined. Varieties of prototypes are analyzed. The conditions for their testing are described. The conditions for their testing are described. It is proposed forms of tests that have to understand consumer reaction.